Kajian Etnobotani Suku Kaili Tara di Desa Binangga Kecamatan Parigi Tengah Kabupaten Parigi Moutong Sulawesi Tengah - Zulfiani Zulfiani; Eny Yuniati; Ramadhanil Ramadhanil (Biocelebes, 2013)
Ethnobotany is one of science that studies the relationship between botany (plants) associated with ethnic (community groups). This research gets Etnobotani's Study title Kaili's Tribe Par at Silvan Binangga Parigi's district Intermediates Parigi Moutong's regency at Intermediate Sulawesi. This research used survey method through the exploration in the field. Data collection of plant species conducted by in depth interview conducted by interviews and open-ended interview. Data analysis used the cultural significance index (ICS) and the percentage of plant use. Based on these studies found that plants used as food by 44 species, 15 types of spices, drugs 43 types, 4 types of animal feed, customs and religious rituals 13 species, 12 kinds of decoration, coloring and aromatic 7 types, 11 types of fuel and for building materials and furnishings as much as 7 types. Key words: Ethnobotany, useful plants, ICS, Binangga village.